Hospital at Home‐Plus: A Platform of Facility‐Based Care. Issue 3 (27th November 2018) - DeCherrie, Linda V.; Wajnberg, Ania; Soones, Tacara; Escobar, Christian; Catalan, Elisse; Lubetsky, Sara; Leff, Bruce; Federman, Alex; Siu, Albert
Abstract : OBJECTIVES: To describe the evolution of a hospital at home (HaH) program to a HaH with a 30‐day posthospitalization transition period (HaH‐Plus) and results of a retrospective review of cases. DESIGN: After launching HaH‐Plus, we used the same interdisciplinary clinical team to provide acute home‐based care for a broader range of home‐based acute‐level services than originally conceived in the Hospital at Home model. These included a palliative care unit at home (PCUaH), an observation unit at home (OUaH), a post‐acute care rehabilitation at home (RaH), and a program for the hospital averse – those patients needing to be in the hospital but who refuse. SETTING: Urban health system. PARTICIPANTS: Individuals 18 years or older residing in specified catchment area with Medicare fee‐for‐service or accepted Medicare/Medicaid Advantage plans requiring facility‐based care. INTERVENTION: Provision of facility‐based acute‐level care at home to 685 participants. MEASUREMENTS: Length of stay, readmission, and mortality. RESULTS: HaH‐Plus cared for 685 individuals. The PCUaH had the oldest participants (mean age 87), and all groups were predominantly female and dually eligible for Medicare and Medicaid. Diagnoses and length of stay were similar in all groups except that those in RaH had a larger group of diagnoses, than those accepted in to HaH‐Plus and those in OUaH had a shorter stay. Rate of readmission was highest for RaH (19%). Mortality during the active treatment episode was highest for PCUaH and hospital averse as compared to HaH‐Plus, OUaH and RaH. CONCLUSION: Providing a broader range of facility‐based care in the home has significant advantages for patients and increases the scalability of HaH. Developing a spectrum of services was possible by leveraging a robust, 24‐hour HaH team. Community‐ and home‐based care could become a greater part of the U.S. healthcare system if a platform of HaH services along with advances in technology and payment models were developed. J Am Geriatr Soc 67:596–602, 2019.